2004
DOI: 10.1021/ac030344i
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Biomolecules in a Capillary Electrophoresis−Chemiluminescence Detection System

Abstract: Direct detection of biomolecules, such as alpha-amino acids, peptides, and proteins, was accomplished using a capillary electrophoresis-chemiluminescence detection system, in which a luminol-hydrogen peroxide-Cu(II)-catalyzed chemiluminescence reaction was utilized. Biomolecules migrated in the capillary, where they mixed with luminol and the Cu(II) catalyst included in the running buffer. The capillary outlet was inserted into a batch-type chemiluminescence detection cell with hydrogen peroxide-supplemented e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 23 publications
0
66
0
Order By: Relevance
“…Chemiluminescent detection of peptides and proteins labeled with luminol was applied to CZE [123]. For hemoglobin, a detection limit of 1.2610 27 M (0.6 fmol) was achieved.…”
Section: Other Detection Methodsmentioning
confidence: 99%
“…Chemiluminescent detection of peptides and proteins labeled with luminol was applied to CZE [123]. For hemoglobin, a detection limit of 1.2610 27 M (0.6 fmol) was achieved.…”
Section: Other Detection Methodsmentioning
confidence: 99%
“…The increased CL intensity was probably caused by the increased catalytic ability of Cu (II) after formation of Cu (II)-analyte complex. Tsukagoshi (37) suggested that the catalytic ability of Cu (II) is maximal when two of its coordination sites are occupied by a ligand, and the chelation reactions between Cu (II) and isoniazid (38)/p-aminosalicylic acid (39,40) have been reported in the literature.…”
Section: Principle Of Detection Of Iso and Pasmentioning
confidence: 99%
“…When running buffer was used to prepare the working solution, the CL intensities of the analytes decreased with time gradually after preparation. The reason was probably that Cu (II) formed a complex with four occupied sites prior to injection (37). To overcome this problem, H 3 BO 3 buffer only with luminol was used to prepare working solution, and no significant decrease of CL intensity was found.…”
Section: Preparation Of Working Solutionmentioning
confidence: 99%
“…[1][2][3][4] We also analyzed many types of sample, including metal ions, metal compounds, amino acids, peptides, proteins, nucleic acids, saccharides, phenolic compounds, fluorescence compounds, and liposomes, using these systems. [5][6][7] We have determined the significant features of CE with CL detection systems through our previous research. 8,9 Naturally, while absorption and fluorescence detection in CE are carried out in an on-capillary manner, CL detection is brought about by endcapillary (postcolumn) detection.…”
Section: Capillary Electrophoresismentioning
confidence: 99%